Shikara ride, Jammu & Kashmir - Mansi Khanna (Opticon1826, 2014)
Shikara boats are often used in Kashmir as a means of transportation and for fishing. The poor sometimes convert these into shelters as floating homes. Shikaras are a big tourist attraction in the valley as foreigners flock to take a ride in the Dal Lake, fondly known as the "Jewel in the crown of Kashmir". It stretches to an area of 18 square kilometers, and is surrounded by parks and gardens built during the Mughal Area. This photograph was taken during a boat ride in 2013 in Srinagar, the summer capital of the state of Jammu & Kashmir, India. Jannat-e-Kashmir (Heaven on Earth)